Evaluation of Oropharyngeal Dysphagia in Patients Who Underwent Percutaneous Endoscopic Gastrostomy: Stratification Risk of Pneumonia. Issue 2 (14th April 2019) - Chang, Wei‐Kuo; Huang, Hsin‐Hung; Lin, Hsuan‐Hwai; Tsai, Chen‐Liang
Abstract: Background: Aspiration pneumonia is the most common cause of death in patients who undergo percutaneous endoscopic gastrostomy (PEG). This study aims to evaluate the severity of oropharyngeal dysphagia and predict the risk of pneumonia in such patients, using upper gastrointestinal endoscopy. Methods: Endoscope examined the pharyngolaryngeal region in patients who underwent PEG. The severity of oropharyngeal dysphagia was evaluated according to the amount and location of pooling of secretions in the pharyngolaryngeal region. Overall, 55 patients showed absent or minimal amount of secretions (control group), 10 patients showed moderate‐to‐large amounts of secretions filling the pyriform sinus (pharyngeal group), and 23 patients showed secretions entering the laryngeal vestibule (laryngeal group). Demographic data, swallowing level scale, and occurrence of pneumonia were recorded. Results: The incidence of pneumonia was the highest in the pharyngeal group (70.0%), followed by that in the laryngeal (60.9%) and control groups (30.9%; P  = 0.010). Multivariable regression showed that risk of pneumonia was significantly higher in the pharyngeal and laryngeal groups. Cumulative incidence rate of pneumonia was significantly higher in the laryngeal and pharyngeal groups than in the control group (log‐rank test, P  = 0.001). Mortality rate was significantly higher in patients with suboptimal protective cough reflex than in others (50.0% vs 5.9%, P =  0.034). Conclusion: Accumulation of abnormal amounts of secretions in the pyriform sinus or in the laryngeal vestibule increased the risk of the hospital admission following pneumonia in patients who underwent PEG. The mortality rate was higher in patients with suboptimal protective cough reflex.